KAJIAN KOHESI GRAMATIKAL DAN LEKSIKAL PADA PEMBERITAAN BAHASA INDONESIA DIRESMIKAN UNESCO SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR TEKS BERITA KELAS VII SMP - Zenia Carolita Putri; Dewi Herlina; Sinta Rosalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Text is a series of sentences that form meaning. A text can convey its contents correctly if it is able to use good language, making it easier for listeners or listeners to understand what is being conveyed. Discourse can be said to be a unity of meaning in a language that is related to the context of a composition, a text, writing, or a complete and intact document is called a discourse. The form of discourse can be seen in various media, namely digital news media. This study aims to analyze grammatical and lexical cohesion in Indonesian language news reports inaugurated by UNESCO. The data used are news texts taken from digital news media kompas.com and detik.com. The methodology of this study uses a qualitative descriptive approach. This study focuses on the identification and description of cohesion markers that support the integrity and integration of meaning in the news text. The results of the analysis of grammatical cohesion found 28 grammatical aspect data consisting of 9 data references, 5 data substitutions, 6 data ellipsis, and 8 data conjunctions. The results of the analysis of 132 lexical cohesion markers in the form of 27 data repetition, 24 data synonymy, 14 data antonymy, 24 data collocation, 21 data hyponymy and 22 data equivalence. This teaching material focuses on reading and viewing elements, with the aim of improving students' literacy skills in understanding news texts deeply and critically. This study contributes to the understanding of text structure and innovative and contextual learning development strategies.